"An Army of Civil Servants": Max Weber and Émile Durkheim on Socialism. Issue 4 (17th December 2014) - Dawson, Matt
Abstract: This paper is a comparison of the views of Max Weber and Émile Durkheim on socialism; these two have yet to be compared on this topic. They offered shared critiques of socialism, but differed in assessment of its overall worth, with Durkheim being more welcoming. After considering possible explanations for this divergence I argue it reflects the contrasting methodologies adopted by both. Whilst Weber places questions of the "value" of socialism solely in the conscious of the individual, and therefore beyond sociology, Durkheim sees this as a social question and therefore part of the practical concerns of sociologists.